Process simulation of green ammonia production from oil palm frond (OPF) waste via gasification: a technical feasibility study - Rudy Heryadi; Hendera Hendera (Universitas Lambung Mangkurat, 2026)
Indonesia, as a leading palm oil producer, generates massive quantities of Oil Palm Frond (OPF) waste that are currently underutilized, especially in Kalimantan and Sumatra. This study evaluates the technical feasibility of converting OPF biomass into green ammonia as a sustainable fuel alternative. A steady-state process simulation was developed using Aspen Hysys that integrates biomass gasification, syngas cleaning, a Water-Gas Shift (WGS) unit, and a high-pressure ammonia synthesis loop. Based on a feedstock input of 16,000 kg/h, the simulation yielded an ammonia production rate of 8,381 kg/h, achieving a biomass-to-ammonia conversion ratio of approximately 1.9:1. The product purity reached 97.18 mol% (equivalent to 98–99 wt%), meeting industrial standards for commercial applications. Plant performance analysis indicated an energy conversion efficiency of 55% and a specific energy consumption of 1.03 kWh/kg NH3 across the compression and synthesis sections. These results confirm that the gasification of OPF is a technically viable pathway for green ammonia production, offering a promising solution for biomass waste management and supporting Indonesia's transition toward renewable energy.